2016
DOI: 10.1002/aenm.201600751
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Non‐Aqueous Electrolyte for Rechargeable Li–O2 Batteries

Abstract: The rechargeable Li–O2 battery has attracted much attention over the past decades owing to its overwhelming advantage in theoretical specific energy density compared to state‐of‐the‐art Li‐ion batteries. Practical application requires non‐aqueous Li–O2 batteries to stably obtain high reversible capacity, which highly depends on a suitable electrolyte system. Up to now, some critical challenges remain in developing desirable non‐aqueous electrolytes for Li–O2 batteries. Herein, we will review the current status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
142
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 239 publications
(376 reference statements)
1
142
0
4
Order By: Relevance
“…[13][14][15][16] As demonstrated, the incorporation of active cathode catalyst, which can increase the overall energy storage efficiency by accelerating ORR and OER process, makes sense. Currently, many insightful reviews on Li-O 2 battery have been published from various perspectives, [17][18][19][20][21][22] thus providing an excellent starting point for researchers with the desire to explore the Li-O 2 technology. However, the content reported in these reviews doesn't include the latest development regarding electrocatalyst in Li-O 2 battery.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] As demonstrated, the incorporation of active cathode catalyst, which can increase the overall energy storage efficiency by accelerating ORR and OER process, makes sense. Currently, many insightful reviews on Li-O 2 battery have been published from various perspectives, [17][18][19][20][21][22] thus providing an excellent starting point for researchers with the desire to explore the Li-O 2 technology. However, the content reported in these reviews doesn't include the latest development regarding electrocatalyst in Li-O 2 battery.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [1,4,7,8,9,10,11] have shown that the electrochemical performance of Li–O 2 batteries depends on many factors, such as the nature and microstructure of the O 2 electrode, the formulation of the electrolyte (especially, the composition of the solvent), the possible presence of reactive contaminants (e.g., trace water) and the choice of catalysts. In order to enhance the properties of rechargeable Li–O 2 batteries, most studies have focused on the electrolyte formula, choice, and microstructure design of the O 2 electrode/electrocatalyst, and optimization of the operating parameters [1,3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several potential electrocatalysts that promote ORRs and OERs in Li–O 2 batteries have recently been proposed, including nitrogen-doped carbon, metal oxides, metal nitrides, precious and nonprecious metals, etc. [1,2,6,11,13,14,15,16,17]. Among metal oxides, manganese oxide is a catalyst material of great interest owing to its low cost, environmental friendliness, abundance, and electrocatalytic activity for ORRs in Li–O 2 batteries [1,6,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…13 There are multiple scientic challenges which need to be conquered, such as poor capability, low-round-trip efficiency, 1,14 instability of electrolytes 5,9,14 and especially the short cycle life. 5,15 In previous studies, 12,[16][17][18] it was demonstrated that an exquisite cathode and effective electrocatalyst could accelerate the kinetic reactions and thus improve the overall energy storage efficiency. In particular the slow oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) on the cathode are the centre of these problems.…”
Section: Introductionmentioning
confidence: 99%